Architecture of network systems - Serpanos, Dimitrios Nikolaou; Wolf, Tilman (Morgan Kaufmann series in computer architecture and design, 2011)
Network systems require technical skills in computer architecture, design methodologies, algorithm design, and networking. Architecture of Network Systems explains the practice and methodologies that will allow you to solve a broad range of problems in system design, including problems related to security, quality of service, performance, manageability, and more. Leading researchers Dimitrios Serpanos and Tilman Wolf develop architectures for all network sub-systems, bridging the gap between operation and VLSI. Discussing the major challenges in the design of networks and the architectures that have been developed, Serpanos and Wolf provide a systematic treatment of network architectures, from the basics to advanced topics. This is the first book to provide comprehensive coverage of the technical aspects of network systems, including processing systems, hardware technologies, memory managers, software routers, and more. Develops a systematic approach to network architectures, based on the OSI reference model, that is useful for practitioners at every level. Covers both the important basics and cutting-edge topics in network systems architecture, including Quality of Service and Security for mobile, real-time P2P services, Low-Power Requirements for Mobile Systems, and next generation Internet systems